2003
DOI: 10.1590/s0034-71672003000100008
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida em pacientes coronariopatas

Abstract: IntroduçãoAs doenças cardiovasculares (DCV) têm apresentado expressiva prevalência nos quadros de morbi-mortalidade na maioria dos países do ocidente, inclusive em países da América do Sul, como o Brasil. Dentre as DCV destaca-se a coronariopatia como grande causa de morte e incapacidade, na ocorrência de suas manifestações clínicas: infarto do miocárdio (IM), angina pectoris (AP) e a morte súbita. Na literatura, há freqüentes registros sobre a influência da vivência da manifestação do evento isquêmico sobre a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0
8

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 8 publications
5
6
0
8
Order By: Relevance
“…There was a greater proportion of men in our sample, which was also reported in other studies of HRQoL in patients with heart disease (10,(12)(13)(14)(15)(16)(17)(22)(23) .…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…There was a greater proportion of men in our sample, which was also reported in other studies of HRQoL in patients with heart disease (10,(12)(13)(14)(15)(16)(17)(22)(23) .…”
Section: Discussionsupporting
confidence: 86%
“…The age distribution of our study participants was similar to that reported in other studies investigating patients with CAD (10,(13)(14)(15)(16)22) . There was a greater proportion of men in our sample, which was also reported in other studies of HRQoL in patients with heart disease (10,(12)(13)(14)(15)(16)(17)(22)(23) .…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations